Teachers' Perceptions on Student Leadership Traits And Potentials in Malaysian Secondary Schools - Nurul Mardhiah Mohd Nashuha; Haryati Bakrin; Amalia Mahmudah; Anik Isticharoh (Universitas Muhammadiyah Sidoarjo, 2019)
Student leadership is seen to be one of the crucial issues in educational leadership field due to its impact on students, especially for the secondary and tertiary level students. Traits of student leaders are being investigated as one of the factors contributing to the effectiveness of student leadership in school. Categorised as one type of school leadership, student leadership is considered very beneficial for personal development of self-confidence and self-esteem as well as very prudent for the nation. The main purpose of this study is to investigate teachers’ perceptions on student leadership - its definition and benefits - and the shared traits possessed by student leaders. There were two theoretical frameworks used in this study. The first framework is by Northouse (2004) on Traits of a Good Leader, and the second is by Kozes and Posner (2012) on Five Practices of Exemplary Leadership. This qualitative study involved eight respondents who are secondary school teachers from various schools and age groups, using convenience sampling. Semi-structured interview was used in order to gain the teachers’ perceptions. The data was analysed using descriptive thematic approach. The findings revealed that there are ten shared traits of student leaders which are closely related to Northouse’s (2004) traits on good leaders and one concluded definition of student leadership also came out as a result.